Examining users’ emotional responses to YouTube content during the Covid-19 crisis: A cross-country experiment - Papa, Venetia; Constantinou, Elena; Lamprianou, Iasonas (My University, 2025)
This study experimentally investigates people’s emotional responses to different online messages about Covid-19 on YouTube. Participants from the United Kingdom (N = 331), the United States (N = 312), and Greece (N = 306) completed an online experiment. Participants viewed two expert videos: one presenting positive vaccine news, and the other emphasizing the seriousness of COVID-19. After viewing, participants expressed their feelings and reported their level of COVID-related worry. Users reported more endorsement for the video of an expert describing the seriousness of Covid-19. This is the first study using mixed-methods evidence to highlight the importance of involving experts in crisis communication and the buffering effects of positive news amid crises.
Keywords: emotional responses; mixed methods; YouTube content; Covid-19